The Balanced Scorecard Approach to Assess the Influence of ERPS and SCM Usage with Strategic Alignment as a Moderator - Weli Weli (Bina Nusantara University, 2018)
The purpose of this research was to examine whether the Enterprise Resource Planning System (ERPS) usage by Indonesian companies affected the firm performance based on the balanced scorecard approach directly or moderated by strategic alignment. This research also assessed the performance between companies that applied ERPS with Supply Chain Management (SCM) and the companies applying ERPS without SCM. Data collection was conducted from October 2010 to April 2011 using questionnaires sent to respondents by e-mail and directly to the company. The sampling method used was convenience sampling by visiting companies in the survey. The final number of samples were 63 companies. Data analysis was conducted by using Structural Equation Model (SEM). The results show that ERPS usage directly affects firm performance as measured by the balanced scorecard that includes financial perspective, customer perspective, internal process perspective, and learning and growth perspectives. Moreover, the strategic alignment has been proven as a moderating variable in the relationship between ERPS usage and the firm performance. Finally, the modules addition such as SCM significantly affects the firm performance.